Four Essays in Accounting Theory and Some Accounting Terms and Concepts: A Report of a Joint Exploratory Committee of the Institute of Chartered Accountants in England and Wales and the National Institute of Economics and Social Research (Book). - Hendrickson, Harvey S. (The Accounting Review, 1985)
Reviews the book "Four Essays in Accounting Theory and Some Accounting Terms and Concepts: A Report of a Joint Exploratotory Committee of the Institute of Chartered Accountants in England and Wales and the National Institute of Economics and Social Research," by F. Sewell Bray.